Intra-Household Commuting Choices and Local Labour Markets - Jennifer Roberts; Karl Taylor (Institute for the Study of Labor (IZA), 2015)
While the job search literature has increasingly recognised the importance of the spatial distribution of employment opportunities, local labour market conditions have been a notable omission from much of the empirical literature on commuting outcomes. This study of the commute times of dual earner couples in England and Wales finds that local labour market conditions are closely associated with commute times and their effects are not gender neutral. Male commute times are much more sensitive to local unemployment rates than women's; where women earn less than one-third of household income, their commute times do not seem to be sensitive to local unemployment. In addition, the more conducive the local labour market is to female employment, the less time women spend commuting. On average the 'female friendliness' of the local labour market has no effect on male commute times, but in households where women earn the majority of household income, men commute further if the local labour market is female friendly. We also show that it is important to account for the heterogeneity of household types; there are important differences in our results according to female income share, housing tenure, mover status and mode of travel.
Keywords: D19; J24; R40; 330; commuting; local labour market; dual earner households